Central nervous system paracoccidioidomycosis: case report and review. - Tristano, Antonio G; Chollet, María Eugenia; Willson, María; Perez, Julián; Troccoli, Marcos (Investigación Clínica, 2009)
Paracoccidioidomycosis is a systemic infection caused by a dimorphic fungus (Paracoccidioides brasiliensis). The most common lesions frequently occur in the bucopharinx mucosa. Other lesions occur in the adrenal glands, liver, bone, gastrointestinal tract, lungs and nervous system. We report here a case of neuroparacoccidioidomycosis. The patient was a 49 year-old male, who consulted due to neurological symptoms (cephalalgia, speech difficulty and one tonic clonic seizure with urinary incontinence) of eight months duration. Upon physical examination it was observed an emaciated male with nail clubbing, a skin ulcer with raised edges and a crusted bottom of 4 í— 2 cm in diameter located in the right supraclavicular region and an ulcerated lesion in the left tonsil with edema. The rest of the physical examination reveled a discrete left side hemiparesis and pulmonary rales in the left hemitorax. The fungus was identified through direct examination of cerebrospinal fluid (CSF). The histopathology of suprarenal, lungs, brain and skin showed multiple paracoccidioidal granulomas. To the best of our knowledge, this is the third case reported in the literature. We review the literature on the pathogenesis and prevalence of neuroparacoccidioidomycosis.